Insomnia in Alcohol-Dependent Patients: Prevalence, Risk Factors and Acamprosate Effect: An Individual Patient Data Meta-Analysis. (30th March 2018) - Perney, Pascal; Lehert, Philippe
Abstract : The aim of the study is to confirm the efficacy of acamprosate to reduce insomnia using an individual patient data meta-analysis. Twelve studies were found including 3508 patients. After a 6-month follow-up, the mean insomnia decrease over baseline was −26% and −45% for the placebo and acamprosate groups, respectively ( P < 0.001). Abstract: Aims: The prevalence of insomnia ranges from 36% to 91% in alcohol-dependent patients and may persist after alcohol withdrawal. Acamprosate has been shown to decrease insomnia in abstinent patients. Based on a large clinical trial database, the aim of the present study is to assess the efficacy of acamprosate in reducing insomnia, and if indeed it does reduce insomnia, to better understand its action mechanism. Short Summary: The aim of the study is to confirm the efficacy of acamprosate to reduce insomnia using an individual patient data meta-analysis. Twelve studies were found including 3508 patients. After a 6-month follow-up, the mean insomnia decrease over baseline was −26% and −45% for the placebo and acamprosate groups, respectively ( P < 0.001). Methods: An individual patient data meta-analysis selected all the randomized trials of acamprosate in which insomnia was documented. Our main endpoint was insomnia change after a 6-month follow-up, measured by the validated Short Sleep Index (SSI) derived from the Hamilton Depression and Anxiety Scale. The meta-analysis was conducted using a two-level multilevel (patient/trial) mixed model with random treatment effect, random study effect and adjusting for baseline severity covariates. Results: Twelve studies were found including 3508 patients, 59.8% of whom were suffering from insomnia (95% CI 58.1–61.4). Psychiatric history, severe addiction, living alone and abnormal gamma-GT levels were found to be the risk factors of insomnia. After 6 months, the mean SSI decrease over baseline was −26% and −45% for placebo and acamprosate, respectively (treatment effect = 19%, 12.5–25.5; P < 0.001). By using a univariate mediation model, we found that the mediating effect of abstinence on insomnia accounted for 55.7% of the overall effect of acamprosate on insomnia reduction. Conclusions: Insomnia is prevalent among alcohol-dependent patients. It decreases spontaneously with abstinence but more frequently with acamprosate treatment.